Side Effects of Large-Scale Assessments in Education. (September 2019) - Emler, Trina E.; Zhao, Yong; Deng, Jiayi; Yin, Danqing; Wang, Yurou
Purpose: In line with a recent call for side effects research in education, this article aims to synthesize the major concerns that have been raised in the literature concerning large-scale assessments (LSAs) in education. Design/Approach/Methods: The researchers endeavored to complete a deep review of the literature on LSAs to synthesize the reported side effects. The review was synthesized thematically to understand and report the consequences of the ongoing push for the use of LSA in education. Findings: Thematic analysis indicated overarching side effects of LSA in education. We discuss why negative side effects exist and present evidence of the most commonly observed side effects of LSA in education, including distorting education, exacerbating inequity and injustice, demoralization of professionals, ethical corruption, and stifling of innovation in education. Originality/Value: While concerns about the use and misuse of LSA in education are not new and have been discussed widely in the literature, rarely have they been discussed as inherent qualities and consequences of LSAs that can do harm to education.